Effect Of The Level Of Participation In Sportive Activities On Trust In Teachers And Identification Level With School l - İhsan Kuyulu; Enes Beltekin (Türk Spor ve Egzersiz Dergisi)
The study was performed out to examine the effect of high school students' level of participation in sports activities on teacher confidence and identification with school. The research group consists of a total of 302 students, 211 males and 91 females studying in different types of high schools in Şanlıurfa during the 2018-2019 academic year. In order to gain data for the purpose of the study, “Identification with School Scale” and “Teacher Trust Scale” were used. The students participating in the study were asked personal information questions regarding their demographic characteristics. The study was carried out in SPSS 22 statistical package program and the degree of significance was taken as 0.05. Independent Sample T (Independent Sample) test was used in binary comparisons, One-Way Variance Analysis (OneWayAnova) was used in multiple comparisons, and the correlation (Pearson) test was used to determine the relationship between variables. According to the responses given by the students who participated in the study, there was a significant difference between the groups in terms of facility adequacy in the school, the efficiency of the sports activities and the type of school, for the level of the students' confidence in the teacher and their identification with the school, but there was a significant difference between the groups in terms of their identification with the students. According to the results of the correlation analysis, a positive correlation was found between the students' confidence levels and their identification with the school. Finally, according to the regression results obtained, it was determined that the adequacy of the club activities and facilities in the school had a positive effect on the students' identification with the school and their confidence in the teacher.